A Study of High School Students’ English Learning Enjoyment (ELE) in China - Zhi , Yibo; Liu, Honggang (LPPM Universitas Lancang Kuning. Pekanbaru. Indonesia, 2021)
English Learning Enjoyment (ELE) potentially sustains students’ motivation of English learning, especially under China’s fresh context where National English Curriculum Standards for Senior High Schools issued in 2017 has directed teachers to cultivate students’ core competencies of English as a subject. Its theoretical framework was established by Dewaele and MacIntyre (2014) on Foreign Language Enjoyment (FLE) and then subcategorized by Li Chengchen et al. (2018) into ELE-Private, ELE-Teacher, and ELE-Atmosphere. The three dimensions have thus made it possible for the following quantitative research, where an enormous space remains on senior high school students in China, despite exhaustive studies beforehand with either overseas background or distinctive educational contexts. This quantitative study will concentrate on the general levels of ELE, both overall and for each dimension. Thus with Li Chengchen et al.’s (2018) ELE Scale came the investigations of 351 senior high school students of all grades with diverse academic levels, whose data were analyzed through SPSS in terms of general levels (both mean values and standard differentiations). The results have looked at an intermediate and converging level of Overall ELE with a more prominent level of ELE-Teacher than ELE-Private and ELE-Atmosphere. Inspired by the results comes a disclosure of students’ positivity in English learning under the guise of their inclination to teachers’ efforts instead of automatic drive or constructive environment for authentic language development. Thus an integrated approach is recommended by dint of an elaborate picture of ELE-Private and ELE-Atmosphere to reclaim the lost authentic “self” of senior high school students.